2009
DOI: 10.1002/mrc.2520
|View full text |Cite
|
Sign up to set email alerts
|

Determination of metabolite profiles in tropical wines by 1H NMR spectroscopy and chemometrics

Abstract: Traditionally, wines are produced in temperate climate zones, with one harvest per year. Tropical wines are a new concept of vitiviniculture that is being developed, principally in Brazil. The new Brazilian frontier is located in the northeast region (São Francisco River Valley) in Pernambuco State, close to the equator, between 8 and 9 degrees S. Compared with other Brazilian and worldwide vineyards, the grapes of this region possess peculiar characteristics. The aim of this work is a preliminary study of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…In a study of wines produced in the Bordeaux region in France, Pereira et al [51] showed that the NMR metabolic profile of wines was affected within a given wine cultivar by soil type (gravely, sandy, or clay), but vintage and cultivar effects were more dominant. Da Silva Neto et al [52] Some other agronomical factors that have been studied include the effect of grape maturity and health on wine quality. Chang et al [53] studied the effect of harvest time on the quality and metabolite composition of wines obtained from grapevine cv.…”
mentioning
confidence: 99%
“…In a study of wines produced in the Bordeaux region in France, Pereira et al [51] showed that the NMR metabolic profile of wines was affected within a given wine cultivar by soil type (gravely, sandy, or clay), but vintage and cultivar effects were more dominant. Da Silva Neto et al [52] Some other agronomical factors that have been studied include the effect of grape maturity and health on wine quality. Chang et al [53] studied the effect of harvest time on the quality and metabolite composition of wines obtained from grapevine cv.…”
mentioning
confidence: 99%
“…Simple 1 H NMR methods provide a wealth of information about liquid samples, such as biomass hydrolysates, including both carbohydrate and hydrolysate by-product compositions. Mixture analysis of NMR spectra is well developed, with many software applications making analysis straightforward and reliable (da Silva Neto et al, 2009;Powers, 2009;Spraul et al, 2009;Da Silva et al, 2013). Traditionally, sugar analysis in biomass hydrolysates has been performed using integration of the anomeric proton region between 4.4 and 5.4 ppm against a reference standard (Kiemle et al, 2003;Mittal et al, 2009), but peak overlap occurs for several sugars and the large water peak at 4.8 ppm often makes integration of these peaks impossible.…”
Section: Nmr For Biomass Sugar and Fatty Acid Compositionmentioning
confidence: 99%
“…Simple 1 H NMR screening methods are able to detect the sugar components in liquid hydrolysates, making this an attractive method for high throughput screening. There is a wealth of information published about mixture analysis with NMR in applications including drug discovery (Powers, 2009) and quality control of wine (da Silva Neto et al, 2009) and fruit juices (Spraul et al, 2009). In biomass hydrolysates, sugar concentrations have been determined with 1 H NMR by relying on the anomeric proton region between 4.4 and 5.4 ppm where the signals from the individual sugars are integrated against a known reference compound that has been added to the sample (Kiemle et al, 2004; Mittal et al, 2009).…”
Section: Introductionmentioning
confidence: 99%